Level of Implementation of Drug Rehabilitation Program, Treatment and Intervention for Persons Who Use Drugs (PWUD) in Basud, Camarines Norte, Philippines - Avengoza-Almadrones, Rosalie J.; Babala, John Kevin A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The study specifically assessed the level of implementation of the Drug Rehabilitation Program, treatment and intervention for Persons Who Use Drugs (PWUD) in Basud, Camarines Norte. It employed descriptive research where 300 respondents participated as respondents. As to the findings, in terms of community preparation PNP Basud initiates advocacy programs on drug education in the community. The least implemented practice was initiating activities in organizing screening for person who use drugs. Meanwhile, in terms of screening, it was found that MHO Basud initiates accomplishing intake form during the screening process. The least practice was initiating schedule check-up by MHO Basud. In terms of assessment, the results showed that MHO Basud ensures other assessment of other mental health conditions using mhGAP IG. The least practice, however, was ensuring request for laboratory/diagnostic test by the MHO Basud. In terms of implementation of intervention, it was revealed that MHO Basud implements community-based treatment for person who uses drugs. The least practice was implements inpatient treatment for person who uses drugs by MHO Basud. Finally, in terms of aftercare program, it was revealed that DILG Basud undertakes community reintegration for person who formerly uses drugs. The least practice, however, was ensuring follow-up for person who formerly uses drugs by the DILG Basud. Comprehensive community-based training programs and educational orientation on drug-related treatment, rehabilitation and interventions may be continuously provided to the implementers of interventions to raise public awareness on the essence, objectives and processes involved in community-based drug rehabilitation.